School-University Partnerships in English Language Teacher Education Tensions, Complexities, and the Politics of Collaboration - Chan, Cheri (SpringerBriefs in Education, 2016)
This book addresses the complex issues that arise in school-university collaborative action research projects. Employing sociocultural perspectives on examining professional practices of in-service teachers, it examines the complexities of negotiating beliefs, identities and interpersonal relations when educators from two different institutional cultures collaborate. Specifically, the book explores issues such as the discourses that are operative in school-university collaboration for English language teacher education; the way in which beliefs, interpersonal relations and identities are negotiated in school-university partnership; what tensions and complexities operate in collaborative action research discourse in an educational context; and how school-university collaboration can be achieved. The book adopts a critical perspective and provides arguments from a non-Western sociocultural perspective.